EARLY DETECTION OF URIC ACID LEVELS IN THE RW 14 COMMUNITY GROUP, BOJONGGEDE VILLAGE, BOGOR REGENCY - Candra Kirana, Mutiara; Fatimah, Ratih (LPPM Univ. Ibn Khaldun Bogor, 2022)
Over time the number of gout sufferers is increasing and can be found all over the world, regardless of human race. Several risk factors that can cause a person to develop gout are age, lack of physical activity, and obesity (obesity). In a pandemic situation like now, it requires people to be at home more often, activities are reduced and there is an increase in the tendency of an unfavorable lifestyle. Therefore, by holding a health check that aims to at least help provide services for the community to still be able to check uric acid levels in the hope that people can pay more attention to their lifestyle in order to keep uric acid levels from increasing. This activity was held on September 26, 2021 at the Baiturrahman Mosque Hall, and the results showed that of the 20 participants, 16 (80%) had normal uric acid levels and 4 (20%) had high uric acid levels.